To perform polynomial addition correctly, we need to combine like terms from both polynomials. Here we have the two polynomials:
- \(2x^2 + 6x + 1\)
- \(3x^2 + 3x + 9\)
Let's add these two polynomials step by step:
- Combine the \(x^2\) terms: \(2x^2 + 3x^2 = 5x^2\)
- Combine the \(x\) terms: \(6x + 3x = 9x\)
- Combine the constant terms: \(1 + 9 = 10\)
Putting it all together, we get:
\[ (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 5x^2 + 9x + 10 \]
Thus, the correct example demonstrating polynomial addition is:
\((2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 5x^2 + 9x + 10\)